IL-6 Promotes Islet β-Cell Dysfunction in Rat Collagen-Induced Arthritis - Huan Jin; Yaogui Ning; Haotong Zhou; Youlian Wang (Journal of Diabetes Research)
The aim of this study was to explore the possible mechanism of rheumatoid arthritis- (RA-) related abnormal glucose metabolism. The model of collagen-induced arthritis (CIA) was established by intradermal injection of type II collagen into Wistar rats; complete Freund’s adjuvant injections were used as the control group. Fasting plasma glucose (FBG) was measured by the glucose oxidase method. Fasting insulin (FIns) and the expressions of IL-6 were detected by ELISA. Islet caspase-3 was examined by immunohistochemistry. On day 17 after immunization, FBG of the CIA group showed an elevated FBG value compared with the control group. Meanwhile, the FIns of group CIA was lower when compared with the control group. Interestingly, the inflammatory cytokine IL-6 expression was significantly increased when compared with the control group. As expected, the abnormal glucose metabolism was accompanied by the increased IL-6 expression. Furthermore, in line with the upregulated IL-6 expression, the apoptosis related enzyme caspase-3 was also markedly increased. These data showed that the elevated FBG in CIA may be associated with the reduced FIns level secondary to the overapoptosis of pancreas islet cells induced by IL-6.